Naturally Occurring Capsid Protein Variants of Human Papillomavirus Genotype 31 Represent a Single L1 Serotype - Bissett, Sara L. (J Virol, 2015)
We investigated naturally occurring variation within the major (L1) and minor (L2) capsid proteins of oncogenic human papillomavirus (HPV) genotype 31 (HPV31) to determine the impact on capsid antigenicity. L1L2 pseudoviruses (PsVs) representing the three HPV31 variant lineages, variant lineages A, B, and C, exhibited comparable particle-to-infectivity ratios and morphologies. Lineage-specific L1L2 PsVs demonstrated subtle differences in susceptibility to neutralization by antibodies elicited following vaccination or preclinical L1 virus-like particle (VLP) immunization or by monoclonal antibodies; however, these differences were generally of a low magnitude. These data indicate that the diagnostic lineage-specific single nucleotide polymorphisms within the HPV31 capsid genes have a limited effect on L1 antibody-mediated neutralization and that the three HPV31 variant lineages belong to a single L1 serotype. These data contribute to our understanding of HPV L1 variant antigenicity. IMPORTANCE The virus coat (capsid) of the human papillomavirus contains major (L1) and minor (L2) capsid proteins. These proteins facilitate host cell attachment and viral infectivity and are the targets for antibodies which interfere with these events. In this study, we investigated the impact of naturally occurring variation within these proteins upon susceptibility to viral neutralization by antibodies induced by L1 VLP immunization. We demonstrate that HPV31 L1 and L2 variants exhibit similar susceptibility to antibody-mediated neutralization and that for the purposes of L1 VLP-based vaccines, these variant lineages represent a single serotype.